REAC-IN Regional Energy Aware Clustering Protocol in Wireless Sensor Network - Singh, Jagdeep; Bala, Manju; Varsha (International Journal of Computer Sciences and Engineering, 2025)
An appropriate clustering algorithm for grouping sensor nodes can increase the energy efficiency of WSN’s. Here, This paper is proposing a new regional energy aware clustering method using isolated nodes for WSNs, called Regional Energy Aware Clustering with the Isolated Nodes ( REAC-IN ). In REAC-IN, CH's are selected based on weight. To prolong network lifetime, the regional average energy and there distance between these sensors and the sink are used to determine that whether the isolated node sends its data to CH node in the previous round or to the sink. The simulation results of the current study revealed that the REAC-IN out performs other clustering algorithms.